2015
DOI: 10.4269/ajtmh.14-0627
|View full text |Cite
|
Sign up to set email alerts
|

Dot-ELISA Rapid Test Using Recombinant 56-kDa Protein Antigens for Serodiagnosis of Scrub Typhus

Abstract: Abstract. We developed a rapid dot-enzyme-linked immunosorbent assay (dot-ELISA) using the combination of recombinant 56-kDa protein antigens that exhibited broad reactivity with serum antibodies against the four most prevalent strains (Karp, Kato, Gilliam, and TA763) of Orientia tsutsugamushi. The assay is rapid (30 minutes), and can be done at room temperature, and results can be read by the naked eye. Only a simple shaker is required to wash the membrane. Sera from 338 patients suspected of being ill with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…This notion is supported by the results of a dot-ELISA assay based on the same three recombinant protein antigens. Rodkvamtook et al demonstrated that the dot-ELISA assay had very good sensitivity and specificity for ST diagnosis [30]. Our results concluded that the use of these recombinant proteins in ELISA also provided good sensitivity and specificity to diagnose scrub typhus.…”
Section: Discussionsupporting
confidence: 56%
“…This notion is supported by the results of a dot-ELISA assay based on the same three recombinant protein antigens. Rodkvamtook et al demonstrated that the dot-ELISA assay had very good sensitivity and specificity for ST diagnosis [30]. Our results concluded that the use of these recombinant proteins in ELISA also provided good sensitivity and specificity to diagnose scrub typhus.…”
Section: Discussionsupporting
confidence: 56%
“…This is supported by our finding that some patients who had a firm diagnosis of scrub typhus were IgM ELISA negative, despite the time between the onset of fever and convalescent/discharge sampling being more than 10 days (see Table S1 in the supplemental material). An IgM ELISA using well-characterized contemporary local strain recombinant O. tsutsugamushi 56-kDa outer membrane antigens ( 38 , 39 ) could be developed and evaluated in clinical settings using appropriate statistical models. Third, the accuracy of diagnostic tests varies based on prevalence, clinical variability, and availability and timing of convalescent-phase samples ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Once thought to be “junk DNA,” the intergenic noncoding regions account for transcription of 85% of cellular RNA vs. 3% for protein-encoding genes (Elgar and Vavouri, 2008 ; Pennisi, 2012 ). It has become clear that noncoding RNAs, such as lincRNAs, miRNAs, tRNAs among others likely play major roles in gene regulation (Chavali et al, 2011 ; Ching et al, 2015 ; Rodkvamtook et al, 2015 ; Eidem et al, 2016 ; Nam et al, 2016 ). That the majority of AnkA binding sites localize to such regions suggests the need to investigate their potential interactions with ncRNAs.…”
Section: Discussionmentioning
confidence: 99%